Digital-Based Internationalization Strategy In Penetrating The Global Market: A Case Study On MSMEs Who Are Motorcycle Seat Craftsmen In Mojokerto - Moh. Faizin; Sudarmiatin; Heri Pratikto (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This research aims to analyze the internationalization strategy applied by MSMEs of seat materials "CV. Mitra Jaya Sadel" in Mojokerto in an effort to penetrate the global market. The research approach uses qualitative methods with case study designs to explore in depth the processes, challenges, and success factors in international expansion. Data was obtained through in-depth interviews, observations, and documentation of business owners and operational activities related to global marketing. The results of the study show that the strategy of internationalization of MSMEs "CV. Mitra Jaya Sadel" is supported by the use of digital platforms, improving the quality of products based on export standards, and strengthening business networks through international partnerships and marketplaces. In addition, competitive advantages such as competitive prices, production flexibility, and design innovation are key factors in increasing global competitiveness. However, there are several obstacles faced, such as limited access to international market information, obstacles to export regulations, and limited human resources in mastering foreign technology and languages. This research provides implications that strengthening digital literacy, government policy support, and human resource capacity development are important elements in encouraging the successful internationalization of MSMEs in the upholstery industry at the global level.